1997
DOI: 10.1210/jcem.82.12.4590
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Leptin in Colostrum and/or Breast Milk from Lactating Mothers: A Potential Role in the Regulation of Neonatal Food Intake

Abstract: In neonates both nutrients and regulatory factors are transferred from the mother to the suckling infant via milk. In the present work, it has been shown that human milk contains immunoreactive leptin which is identical to intact human leptin by criteria of charge, size, immunorecognition and SDS-PAGE mobility. In experimental animals it was demonstrated that leptin is transferred from the circulation to mothers' milk, then to the infant's stomach and afterwards to infant blood. Maternal leptin in milk may pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
81
0
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 258 publications
(86 citation statements)
references
References 0 publications
4
81
0
1
Order By: Relevance
“…More work is clearly needed to elucidate leptin's physiological role in growth and haemopoiesis as well as its potential role in influencing immunological responses. Recent experimental evidence also suggests that leptin is secreted in the milk and can pass from the infant's gastrointestinal tract to the blood (Casabiell et al, 1997). Thus, in addition to neonatal leptin, maternal leptin in milk may play a role in regulating neonatal food intake and/or growth (Casabiell et al, 1997).…”
Section: Leptin Levels In the Fetus And Neonatementioning
confidence: 99%
“…More work is clearly needed to elucidate leptin's physiological role in growth and haemopoiesis as well as its potential role in influencing immunological responses. Recent experimental evidence also suggests that leptin is secreted in the milk and can pass from the infant's gastrointestinal tract to the blood (Casabiell et al, 1997). Thus, in addition to neonatal leptin, maternal leptin in milk may play a role in regulating neonatal food intake and/or growth (Casabiell et al, 1997).…”
Section: Leptin Levels In the Fetus And Neonatementioning
confidence: 99%
“…Regrettably, the mechanism responsible for this correlation is not understood [15]. Numerous hypothetical links between obesity and breast feeding pertain to the passive nature of bottle-feeding, regardless of the type of milk, versus active suckling when infants are fed directly at the breast [15,16], the hormones and adipokines in breast milk [17][18][19][20][21][22][23], the rates of gastric emptying [24,25], and the rate of the ileal break in emulsions [26]. Accordingly, supplemental in-depth studies comparing the physicochemical properties and digestibility of breast milk and infant formula are imperative.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the physiology of breastfeeding revealed the presence of the two adipokines, leptin [1] and adiponectin [2], hormones, such as IGF-I [3], ghrelin [4], and more recently obestatin [5] and resistin [6] in mother's milk (Table 1). Human milk is a complex biological fluid: leptin and ghrelin are synthesized and secreted into breast milk by the mammary gland and pass from serum into milk.…”
Section: Introductionmentioning
confidence: 99%
“…Leptin is present in human milk [1]; it is produced and secreted by mammary epithelial cells in milk fat globules [29]. Moreover, secretory epithelial cells may transfer leptin from the blood to milk [30].…”
Section: Introductionmentioning
confidence: 99%